Pemanfaatan Media Sosial Sebagai Sarana Promosi Pada UMKM Unstore Karawang - Yohanida, Yohanida; Isyanto, Puji; Sumarni, Neni (Peneliti.net, 2025)
This study examines the impact of online promotion through social media on the promotion of Unstore, a micro, small, and medium enterprise (UMKM) in Karawang City, Indonesia. Unstore currently lacks a presence on social media platforms and faces challenges in revenue generation, intense competition, and promotional difficulties, leading to a lack of public awareness. The research aims to evaluate the effectiveness of social media promotion in supporting Unstore's marketing efforts. Using a qualitative approach, data was gathered through observation, in-depth interviews, and documentation. Findings reveal the significant role of social media in enhancing Unstore's sales performance, with revenue increasing from 20% to 80% through social media promotion.